COVID-19 in patients with juvenile idiopathic arthritis: frequency and severity - Oksana Boyarchuk; Lilya Predyk; Iryna Yuryk (Rheumatology, 2021)
The aim of the study was to determine the frequency and the course of COVID-19 infection in children with juvenile idiopathic arthritis (JIA). The study involved 51 patients with JIA aged 2 to 18 years. Evidence of COVID-19 was found in 10 (19.6%) patients with JIA. COVID-19 infection occurred more often in patients with systemic arthritis (OR = 6.1667, 95% CI: 1.2053–31.5511, p = 0.0289). The course of COVID-19 infection in patients with JIA was generally similar to the course in the pediatric population, despite immunosuppressive therapy. In 3 out of 10 patients the infection caused an exacerbation of JIA, which required therapy escalation.